Soil Quality Index Comparisons Using Fort Cobb, Oklahoma, Watershed‐Scale Land Management Data. Issue 1 (1st December 2014) - Zobeck, Ted M.; Steiner, Jean L.; Stott, Diane E.; Duke, Sara E.; Starks, Patrick J.; Moriasi, Daniel N.; Karlen, Douglas L.
Abstract : The Soil Conditioning Index (SCI) and Soil Management Assessment Framework (SMAF) are two different but complementary methods for evaluating soil quality. Both tools have been widely used, but little is known regarding how they compare and if they provide similar results when the same agricultural management practices are compared. This SCI and SMAF soil quality index (SQI) comparison was conducted on the Fort Cobb Reservoir Experimental Watershed (FCREW) in Oklahoma. Forty‐one loamy and sandy surface soil sites were sampled on the FCREW under (i) annual cropping with conventional tillage (conventional), (ii) annual cropping with either conservation tillage or no‐till (conservation), (iii) cropland that had been converted to perennial grass (managed grass), and (iv) native grass. The SCI and SMAF SQI gave similar assessments, indicating that soil quality within conventional and conservation systems was similar but lower than in either managed or native grassland systems. Simple comparisons of soil properties by textural class showed no significant effects on most soil quality indicator values, and although texture by management subgroups was examined, no clear relationships were detected because of the limited number of sampling sites. The SMAF and SCI indicators and scores were correlated in tilled systems with limited vegetative cover but not for no‐till or forage‐based pasture or grassland systems that were in place for at least 10 yr. The SMAF provided more resolution when evaluating agroecosystem management effects on soil quality, including soil organic C enrichment, especially within forage‐based systems. Recognizing that the SMAF currently does not account for soil loss, we conclude with recommendations for improving the tool, particularly for tilled systems.